Neuroblastoma in the Elderly and SIADH: Case Report and Review of the Literature. (23rd August 2012) - Pellegrino, Micaela; Gianotti, Laura; Cassibba, Sara; Brizio, Rodolfo; Terzi, Alberto; Borretta, Giorgio
Abstract : Objective . To report the rare case of a thymic neuroblastoma, in an elderly woman with SIADH at presentation. Methods . Clinical and biochemical data of the patient are presented and the pertinent literature is reviewed. Results . a 79-year-old woman was admitted into our department with worsening asthenia, severe hyponatremia (114.8 mEq/L), low plasma osmolarity (253 mEq/L), and inappropriate urinary sodium concentration (151 mEq/L). CT scan showed an a large solid inhomogeneous mass in the anterior mediastinum. 18 F-FDG-PET/CT showed uptake in the mass. On continuous 3% hypertonic saline infusion, sodium gradually increased without achieving normal values. The patient underwent surgery, followed by full normalization of sodium levels. Tumor cells were positive for neuroendocrine markers. Thymic neuroblastoma with SIADH was diagnosed. Conclusions . Neuroblastoma is an extremely rare tumor in the elderly. Contrary to children and younger adults, neuroblastoma in older adults is typically localized in the anterior mediastinum and is often associated with SIADH. Moreover, it has mainly local aggressiveness in this age group, without metastatic spread; thus radical surgery achieves cure in most cases.